Filarial nematodes in domestic dogs and mosquitoes (Diptera: Culicidae) from semi-rural areas in Central Chile - Cancino-Faure, Beatriz; González, Christian R.; Piñeiro González, Alejandro; Pinochet, Soledad; Bustos, Sofía; Morchón, Rodrigo; Piñeiro Cazaux, Alejandro; Quezada Aguilar, Ivonne; Salas Espinoza, Merayot; Acevedo Salgado, Rodrigo; Barra Díaz, Carmen; Segovia, Christian; et al. (Frontiers in Veterinary Science, 2024)
Climate change, competent vectors, and reservoir animals are the main factors for developing vectorborne zoonotic diseases. These diseases encompass a significant and widespread category of pathogens (e.g., viruses, bacteria, protozoa, and helminths) transmitted by blood-feeding arthropods, including ticks, fleas, lice, triatomines, mosquitoes, sandflies, and blackflies. In Chile, several studies have explored the role of dogs as reservoirs of vector-borne pathogens; however, there is a lack of research investigating the presence of pathogens in arthropods. Specifically, within the order Diptera, limited knowledge exists regarding their roles as carriers of pathogens. This study aimed to examine the presence of zoonotic filarial nematodes in mosquitoes and dogs within a previously unstudied semirural area of Central Chile. Two hundred samples of dog blood and seven hundred and twenty-four mosquitoes were collected during 2020-2022 and studied for filarial nematodes by PCR. The prevalence of microfilaremic dogs detected by Knott's test was 7.5%, with Acanthocheilonema reconditum being the only species identified. Aedes (Ochlerotatus) albifasciatus was the most abundant mosquito species collected, and 15 out of 65 pools were positive for filarial nematodes. Among these pools, 13 tested positive for Acanthocheilonema reconditum, and two tested positive for Setaria equina through PCR. Additionally, five Culex pipiens specimens were positive for Acanthocheilonema reconditum. Despite the absence of zoonotic filarial species, these findings underscore the significance of monitoring pathogens in mosquitoes and animal hosts and continued research into the dynamics of vector-borne diseases, particularly in unexplored regions.